Active Coping Ibu yang Memiliki Anak Tuna Grahita di Kota Sorong - Almuhaimin Sarnav Ituga; Alman Alman (LPPM IAIN Parepare, 2020)
This study aims to obtain a picture of active coping of mother with a mentally disabled children in terms of decision making abilities, situation improvement, meaning, and positive thinking in overcoming children's problems. This study used a qualitative method with a phenomenological study approach involving three respondents, mother who have biological children with mild, moderate, and severe mental disability. The results of this study indicate that: 1) In terms of decision making ability, mothers have a great desire to plan intensive guidance to the children. 2) In terms of improving the situation, the mother puts the child in a public school after that she transfers to the developmental school, provides therapy and a doctor's examination. 3) Judging from the meaning, the mother can accept the condition of the child, see that the child has a deficiency, and believes that all the gifts of God must have wisdom. 4) In terms of positive thinking, the mother believes that one day the child can grow normally, remain optimistic, hoping that the child's condition can make them go to heaven. Based on the four aspects of active coping, mothers with mildly disabled children show more effort in optimizing their children's abilities. Whereas for mothers who have moderate and severe mentally disabled children, they show more meaning to the situation they are facing.